Attitudes of health professionals to using routinely collected clinical data for performance feedback and personalised professional development. (30th March 2019) - Shaw, Tim; Janssen, Anna; Crampton, Roslyn; O'Leary, Fenton; Hoyle, Philip; Jones, Aaron; Shetty, Amith; Gunja, Naren; Ritchie, Angus G; Spallek, Heiko; Solman, Annette; Kay, Judy; et al.
Abstract: Objectives: To learn the attitudes of health professionals, health informaticians and information communication technology professionals to using data in electronic health records (eHRs) for performance feedback and professional development. Design: Qualitative research in a co‐design framework. Health professionals' perceptions of the accessibility of data in eHRs, and barriers to and enablers of using these data in performance feedback and professional development were explored in co‐design workshops. Audio recordings of the workshops were transcribed, de‐identified, and thematically analysed. Setting, participants: A total of nine co‐design workshops were held in two major public hospitals in Sydney: three for nursing staff (ten participants), three for doctors (15 participants), and one each for information communication technology professionals (six participants), health informaticians (four participants), and allied health professionals (13 participants). Main outcome measures: Key themes related to attitudes of participants to the secondary use of eHR data for improving health care practice. Results: Six themes emerged from the discussions in the workshops: enthusiasm for feeding back clinical data; formative rather than punitive use; peer comparison, benchmarking, and collaborative learning; data access and use; capturing complex clinical narratives; and system design challenges. Barriers to secondary use of eHR data included access to information, measuring performance on the basis of eHR data, and technical questions. Conclusions: Our findings will inform the development of programs designed to utilise routinely collected eHR data for performance feedback and professional development.